Utilization of phosphorus by barley as affected by levels of soil and fertilizer phosphorus - Srivastava, O.P.; Pathak, A.N. (Journal of Soil and Water Conservation, 2022)
The crop absorbed 21.1 and 17.5 percent of its total P2 O5 uptake from fertilizer and utilized 13.0 and 12.6 percent of the phosphorus applied in soil through fertilizar respectively, when grown in soils of low and medium available phosphorus status. Average yield response in respective fields to phosphate application over control were 17.2 and 10.4 percent.